Quantitative insights on de/repolymerization and deoxygenation of lignin in subcritical water - LaVallie, Audrey L; Bilek, Honza; Andrianova, Anastasia; Furey, Kathryn; Voeller, Keith; Yao, Bin; Kozliak, Evguenii; Kubátová, Alena (Bioresource technology, 2021)
The objective of the study was to investigate alkali lignin polymerization/depolymerization pathways in subcritical water (SW) without additives. Following a SW treatment at 200, 250, 275 and 300 °C, the products were subjected to a comprehensive suite of analyses addressing the product speciation and molecular weight (MW) distribution. The MW reduction (1.4 times) in the solid products following the SW treatment indicated a surprisingly reduced impact of cross-linking/repolymerization at 300 °C and lower temperatures. This was further confirmed by thermal carbon analysis (TCA) showing a reduction in pyrolytic charring after the SW treatment. The TD-Py gas chromatography analysis of the SW treated lignin indicated that the solid residue is less oxygenated than the initial lignin (23 vs. 29% as confirmed by elemental analysis). Thus, deoxygenation rather than re-polymerization appears to be the main process route in the absence of catalysts within the temperature range considered.
Keywords: Gel permeation chromatography; voda; polymerizace; lignin; Temperature; Thermal carbon analysis; Water; Pyrolysis; Lignin; Pyrolysis–gas-chromatography-mass-spectrometry; Polymerization; teplota; pyrolýza; Lignin deoxygenation, lignin valorization